Anticholinergic drugs and incident dementia, mild cognitive impairment and cognitive decline: a meta-analysis. (29th June 2020) - Pieper, Nina T; Grossi, Carlota M; Chan, Wei-Yee; Loke, Yoon K; Savva, George M; Haroulis, Clara; Steel, Nicholas; Fox, Chris; Maidment, Ian D; Arthur, Antony J; Myint, Phyo K; Smith, Toby O; et al.
Abstract: Background: the long-term effect of the use of drugs with anticholinergic activity on cognitive function remains unclear. Methods: we conducted a systematic review and meta-analysis of the relationship between anticholinergic drugs and risk of dementia, mild cognitive impairment (MCI) and cognitive decline in the older population. We identified studies published between January 2002 and April 2018 with ≥12 weeks follow-up between strongly anticholinergic drug exposure and the study outcome measurement. We pooled adjusted odds ratios (OR) for studies reporting any, and at least short-term (90+ days) or long-term (365+ days) anticholinergic use for dementia and MCI outcomes, and standardised mean differences (SMD) in global cognition test scores for cognitive decline outcomes. Statistical heterogeneity was measured using the I 2 statistic and risk of bias using ROBINS-I. Results: twenty-six studies (including 621, 548 participants) met our inclusion criteria. 'Any' anticholinergic use was associated with incident dementia (OR 1.20, 95% confidence interval [CI] 1.09–1.32, I 2  = 86%). Short-term and long-term use were also associated with incident dementia (OR 1.23, 95% CI 1.17–1.29, I 2  = 2%; and OR 1.50, 95% CI 1.22–1.85, I 2  = 90%). 'Any' anticholinergic use was associated with cognitive decline (SMD 0.15; 95% CI 0.09–0.21, I 2  = 3%) but showed no statistically significant difference for MCI (OR 1.24, 95% CI 0.97–1.59, I 2  = 0%). Conclusions: anticholinergic drug use is associated with increased dementia incidence and cognitive decline in observational studies. However, a causal link cannot yet be inferred, as studies were observational with considerable risk of bias. Stronger evidence from high-quality studies is needed to guide the management of long-term use.